Electric circuits and network Analysis - Chandrashekharaih, P. M. (New Delhi : CBS, 2007)
This textbook attempts to give a comprehensive material to the students of all the Indian universities studying the subject(s) Electric Circuits and Network Analysrs with special reference to those in electrical science branch in engineering colleges.The textbook contains 15 chapters: 9 chapters are covered under the section Electric Circuits and 6 chapters under Network Analysis.The demarcation between electric circuits and network analysis is only arbitrary and hypothetical as any chapter given in the textbook can be studied under either of the above two concepts. A significant number of typical problems selected from the question papers of various universities are worked out for the benefit of the students. Also an impressive number of unsolved numerical problems are given at the end of each chapter for practice which will give the readers confidence about their understanding of the concepts clearly. A sound knowledge of the fundamentals of electric circuits and network analysis is essential for the understanding of any branch of science such as mechanical hydraulic thermal nuclear traffic flow weather predictionbecause all such systems can be simulated by an electric circuit. The performance of any electrical device or machine is always studied by drawing its electrical equivalent circuit. Hence this book can prove to be useful to the students of other disciplines as well.
pt. 1. Basic circuit concepts (d.c. circuits) -- pt. 2. Mesh current and node voltage analysis -- pt.3 Network theorems -- pt.4. Resonance -- pt.5. Network topology -- pt.6 Locus diagrams -- pt.7. Coupled circuits -- pt.8. Three phase balanced circuits -- pt.9. Three phase unbalanced circuits -- pt.10. Non-sinusoidal wave forms -- pt.11. Initial conditions -- pt.12. Laplace transformation -- pt.13. Network functions -- pt.14. Two part parameters --pt.15. Network synthesis -- Answer to numerical problems .
Includes Index.
Keywords: Electric circuits; Network analysis